The Relationships Among Occupational Safety Climate, Patient Safety Climate, and Safety Performance Based on Structural Equation Modeling - Aghaei, Hamed (J Prev Med Public Health, 2020)
OBJECTIVES: The aim of the present study was to investigate the relationships among hospital safety climate, patient safety climate, and safety outcomes among nurses. METHODS: In the current cross-sectional study, the occupational safety climate, patient safety climate, and safety performance of nurses were measured using several questionnaires. Structural equation modeling was applied to test the relationships among occupational safety climate, patient safety climate, and safety performance. RESULTS: A total of 211 nurses participated in this study. Over half of them were female (57.0%). The age of the participants tended to be between 20 years and 30 years old (55.5%), and slightly more than half had less than 5 years of work experience (51.5%). The maximum and minimum scores of occupational safety climate dimensions were found for reporting of errors and cumulative fatigue, respectively. Among the dimensions of patient safety climate, non-punitive response to errors had the highest mean score, and manager expectations and actions promoting patient safety had the lowest mean score. The correlation coefficient for the relationship between occupational safety climate and patient safety climate was 0.63 (p<0.05). Occupational safety climate and patient safety climate also showed significant correlations with safety performance. CONCLUSIONS: Close correlations were found among occupational safety climate, patient safety climate, and nurses’ safety performance. Therefore, improving both the occupational and patient safety climate can improve nurses’ safety performance, consequently decreasing occupational and patient-related adverse outcomes in healthcare units.